PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR IPS TERPADU SMP MUHAMMADIYAH 1 METRO - Yesi Budiarti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
The background is the number of students who have not yet reached the KKM score or have not yet completed the learning results of the Integrated Ips Class VIIIB in the even semester of Muhammadiyah Middle School 1 Metro 2017/2018 Academic Year. In connection with these problems, the formulation of the problem is "is there any influence on the use of cooperative learning model group type learning on the integrated learning outcomes of Ips Class VIII Even Semester 1 Metro Middle School 2017/2018 academic year". The study aims to determine the effect of the use of cooperative learning model learning group group type on the Integrated Ips learning outcomes of grade VIII students in the even semester of Muhammadiyah 1 Metro Middle School 2017/2018 academic year. The subject of this study was the eighth grade students of Muhammadiyah Middle School 1 Metro 2017/2018 Academic Year. It is an experimental research with instruments in the form of multiple choice questions which amount to 20 and are calculated using the reliability test reliability test. Knowing whether there is influence of the use of cooperative learning model group type learning on Integrated Social Studies learning outcomes of class VIII students, namely by using a simple linear regression formula. The test calculation results show that it can be seen that t count> t table and table can be seen on the G table, at a significance level of 5%, which is 3.77> 1.71. And a significant level of 1% is 3.77> 2.48, which can be seen in the list of G statistics tables. Thus Ho is rejected and Ha is accepted. Thus it can be concluded that there is a positive effect on the use of cooperative learning model learning group group types on Integrated Social Studies learning outcomes in class VIII Muhammadiyah 1 Metro Middle School 2017-2018.  Keywords: Integrated IPS Learning Outcomes, Learning Model (Group Investigation).